1997
DOI: 10.1016/s0924-9338(97)80001-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity in alcoholics treated at an institution with both coerced and voluntary admission

Abstract: SummaryPsychiatric comorbidity in alcoholics admitted to a rehabilitation center on either a voluntary or a coerced basis were studied. A group of 104 alcoholics (37 coerced and 35 voluntarily admitted men; and 21 coerced and ten voluntarily admitted women) with a mean age (SD) of 43 ± 8 years were assessed by means of a Structural Clinical Interview in accordance with the Diagnostic and Statistical Manual (DSM)-III-R (SCID). The interview took place a mean of 7 days after admission. The frequencies of lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Given that compulsory treatment samples exhibit substantial variability in perceptions of coercion [41], readiness to change their behaviour [55] and perceived justifiability of social control tactics [48], it is perhaps not surprising that studies simply comparing referral sources do not provide strong and persuasive evidence with regard to outcomes. Moreover, our review identified several examples of variability in the social 'handling' of mandated treatment clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that compulsory treatment samples exhibit substantial variability in perceptions of coercion [41], readiness to change their behaviour [55] and perceived justifiability of social control tactics [48], it is perhaps not surprising that studies simply comparing referral sources do not provide strong and persuasive evidence with regard to outcomes. Moreover, our review identified several examples of variability in the social 'handling' of mandated treatment clients.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnographic study of Wolf and Colyer [46] identified subtypes of participants exposed to the same drug court procedures. Finally, several studies have begun to investigate patient perceptions of how justified and useful compulsory treatment is, with one investigation reporting high levels of perceived utility for civil commitment [47] and another reporting negative personal reactions to formal and informal mandates [48].…”
Section: What Is the Relationship Between Compulsory Treatment And Comentioning
confidence: 99%
“…One study found that prevalence of psychiatric comorbidity was equivalent for those mandated to treatment for alcohol dependence and those voluntarily seeking treatment (Sallmen, Nilsson, & Berglund, 1997). They also found no gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol addiction frequently occurs within a broader cluster of psychiatric problems. High rates of comorbid disorders are found in clinical samples (Driessen, Veltrup, Wetterling, John, & Dilling, 1998; Sallmen, Nilsson, & Berglund, 1997) as well as in epidemiological surveys (Kessler et al, 1997; Regier et al., 1990). The most common comorbid disorders found in such studies are mood, anxiety disorders, and personality disorders.…”
mentioning
confidence: 99%